Preparation and characterization of pitch coke from oxidized polymerized pitch. Issue 5 (22nd April 2020) - Zhu, Yaming; Sun, Shushuang; Xu, Yunliang; Zhao, Chunlei; Hu, Chaoshuai; Cheng, Junxia; Zhao, Xuefei
Abstract: Refined polymerized pitch (RPP) is a by‐product from the production of mesocarbon microbeads (MCMB). In order to understand the effects of an air oxidation treatment on the microstructure of the synthesized pitch coke, oxidized and polymerized pitch (prepared by oxidation in air with RPP as the raw material) has been used as the raw material to produce pitch coke. The microstructure of as‐prepared pitch coke was determined using optical microscopy, scanning electron microscopy, XRD, and Raman spectroscopy and was combined with a curve‐fitting method. The true density and micro‐strength of each pitch coke was also investigated in this study. The results showed that the oxidation of RPP in air caused a mosaic structure with amorphous carbon in the derived pitch coke. In addition, the micro‐strength of the derived pitch coke improved from 65% to 77%, and the amorphous carbon content also increased from 10.41% to 14.59% after the air oxidation treatment. Therefore, the air oxidation treatment of RPP took place before liquid‐carbonization and was a feasible method for the production of hard carbon.